2016
DOI: 10.1039/c6sm00272b
|View full text |Cite
|
Sign up to set email alerts
|

A light responsive two-component supramolecular hydrogel: a sensitive platform for the fabrication of humidity sensors

Abstract: The supramolecular assembly of anionic azobenzene dicarboxylate and cationic cetyltrimethylammonium bromide (CTAB) formed a stimuli responsive hydrogel with a critical gelation concentration (CGC) of 0.33 wt%. This self-sustainable two-component system was able to repair damage upon light irradiation. Moreover, it was successfully employed in the fabrication of highly sensitive humidity sensors for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…[30] It was found that the lowest critical gelation concentration (CGC)t of orm ah ydrogel was around 0.25 wt %, although the sample required four hours to reach stability.F ormation of the hydrogel with an increased gelator concentrationo f0 .69 wt %r equired only 30 min. Dynamic rheological measurements [31,32] were performed to characterize the rheological behavior of samples with different concentrations of 0.41 wt %a nd 0.15 wt %. The maximum absorption peak showed ab lue-shift with increasing gelator concentration, indicating p-p stacking of the azobenzene moieties.…”
Section: Resultsmentioning
confidence: 99%
“…[30] It was found that the lowest critical gelation concentration (CGC)t of orm ah ydrogel was around 0.25 wt %, although the sample required four hours to reach stability.F ormation of the hydrogel with an increased gelator concentrationo f0 .69 wt %r equired only 30 min. Dynamic rheological measurements [31,32] were performed to characterize the rheological behavior of samples with different concentrations of 0.41 wt %a nd 0.15 wt %. The maximum absorption peak showed ab lue-shift with increasing gelator concentration, indicating p-p stacking of the azobenzene moieties.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Khashab et al reported a light-responsive hydrogel composing anionic azobenzene dicarboxylate and cationic cetyltrimethylammonium bromide (CTAB), such opposite charges direct self-assembly and form self-sustainable hydrogel. 67 Since the UV-irradiation induces the cis-trans change of azobenzene, such feature can be utilized to repair the damage in the surface coating. Furthermore, this heterotypic hydrogel has potential application as a sensor for detecting the humidity environment.…”
Section: Methods For Hydrogelationmentioning
confidence: 99%
“…For example, Khashab et al reported a spontaneous self-assembly of heterotypic hydrogel by mixing an anionic azobenzene dicarboxylate and a cationic surfactant cetyltrimethylammonium bromide. 91 This two-component hydrogel, having a critical gelation concentration of 0.33 wt%, is able to repair damage upon UV light irradiation. The authors coated the hydrogel on gold interdigitated electrodes and tested it as a humidity sensor.…”
Section: Applicationsmentioning
confidence: 99%
“…[26] Theu se of reticular chemistry allowed us to fine tune the triangular window,t he sole entrance to the pore system, size and functionality by substituting the parent longer ligand with arelatively shorter and/or bulkier linkers, which in turn permitted us to assemble isoreticular analogues of RE-fcu-MOFs with tuned adsorption/kinetic properties. [16,[36][37][38] We investigated the sensing properties of fumfcu-MOF thin film on capacitive IDEs for different types of gases/vapors,i ncluding CH 4 ,N O 2, H 2 ,t oluene (C 7 H 8 ), and H 2 S. Theg as-sensing tests were performed using the Lab-VIEW fully automated measurement system. [28][29][30] TheI DE sensors were fabricated using clean room technologies,f ollowing the method reported previously.…”
mentioning
confidence: 99%